Students’ Perceptions on Ice Breaking Activities related to Speaking Skill: Toilet Paper Game and Attendance Checking Questions - Mentari Putrirahayu Prawira; M. Handi Gunawan; Irma D. Lenggani (JELLT (Journal of English Language and Language Teaching), 2025)
The COVID-19 pandemic in 2019 compelled students to stay at home and engage in remote learning for nearly two years, giving rise to the so-called “COVID generation”—students who often face difficulties in classroom communication and anxiety when addressed by teachers. This study aims to perform a qualitative analysis of junior high school students’ perceptions of ice-breaking activities related to speaking skills, specifically the "toilet paper game" and "attendance checking questions." Primary data were collected through post-course reflection questionnaires focusing on students' experiences during the course. Six of the 45 participants were interviewed to further elaborate on their responses. Findings reveal that students largely view these activities positively, as they encourage self-expression and foster better interpersonal connections. Additionally, these activities were perceived to support students in improving their English-speaking skills.